IMPLEMENTASI PEMBELAJARAN FISIKA MELALUI PEMROSESAN TOP DOWN TERHADAP HASIL BELAJAR FISIKA SISWA SMA KELAS X - Aziz, Aisyah (Universitas Tanjungpura, 2017)
This paper describes the results of learning physics that begins with the complex questions that require integration of multiple knowledge to resolve the question. In the learning process, students were trained to plan for a settlement of the problem by first identifying the required amount of physical quantities. This learning guided students to learn according to their needs in solving the problem, in this case using a top down approach to processing. This learning involved studentâ€™s assimilation and accommodation in planning and solving problem involving both, the students will be motivated to participate in the learning process. Physics student learning outcomes obtained after following study at the high category, which showed that not only motivated to follow the lesson, but also they able to achieve a high score Â Keywords: top down approach, physics achievement